Un inside job: adquisiciones corporativas en el mercado de valores chino - Barreda Ayllón, Alonso (2018)
Chinese Stock Exchanges are on the rise. Companies are lucrative and trading is getting sophisticated on a day-to-day basis. Upon this scenario, the following paper takes a closer look on the framework upon which takeovers may happen, the takeovers strategies available in Chinese jurisdiction and the applicable defenses that target companies may use against such attempts.Finally, this paper compares the regulation of Takeovers in China with that of highly developed markets, such as the United Kingdom and the United States. The opinion of this paper is that though unsophisticated Chinese stock exchanges have undertaken proper measures in adapting foreign regulations into its own business idiosyncrasy to regulate the takeover phenomenon.